ECOPHISIOLOGY OF THE JEQUITIBÁ-ROSA AND OF JACARANDA-DABAHIA: MORPHOGENESE, GERMINATION AND INITIAL GROWTH - RÊGO, Gizelda Maia (Scientia Agraria, 2002)
This work studied the influence of some morphologic and environmental factors about two native forest species of natural occurrence in the Atlantic Forest: Cariniana legalis (Martius) Kuntze, jequitibá-rosa and of Dalbergia nigra (Vellozo), jacaranda-dabahia, with the purpose of characterizing the ecophysiological behavior of these species inside of the forest system, describing for each species: the morphologic characterses of the seeds, the germination characteristic, the external morphology of the seedlings and cuttings, the effect of substrate and temperatures in the germination and vigor of the seeds, the effect of levels of photossintheticaly activates radiation (PAR), about the growth and concentration of the leaf chlorophylls in cuttings of these species. For evaluation, in laboratory, of the germination capacity, it was studied the temperatures of 20, 25, 30, 20-30 and 35ºC and the substrate: soil forest, commercial substrate, vermiculita and paper roll. In the nursery, with environment temperature, it was studied the substrate: soil of forest, vermiculita, commercial substrate. The levels of PAR studied were: 34, 44, 64, 70 and 100%. The description of the seeds was done in according to the shape, size, hilum, the micropyle and the form and location of the embryo. The stage of the germination and the external characteristics of the plantlets and cuttings were described. Based in the percentage of germination and emergency speed index, the temperatures of 30 and 20-30ºC, in the substrate vermiculita, favored the germination and vigour for the two species. In the nursery, the best percent of germination was when the soil forest was used. The best percent of germination and vigour, was obtained with the white light for the jequitibá-rosa and red light for the jacaranda-da-bahia. For the two species, the growth in diameter and total dry matter are related with the largest light intensity, while the height, leaf area and chlorophylls a and b, increased when decreased the light intensity. It was observed that the jacaranda-da-bahia presents plasticity and more tolerance to the light than the jequitibá-rosa.